2021
DOI: 10.3390/land10121406
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Scale Features of Regional Poverty and the Impact of Geographic Capital: A Case Study of Yanbian Korean Autonomous Prefecture in Jilin Province, China

Abstract: Poverty is a challenge worldwide. Policy and regulations guiding anti-poverty measures for governments, NGOs, and multilateral institutions have not considered the spatial scale effect of regional poverty, resulting in low-efficiency poverty alleviation actions. This study addressed research gaps by analyzing the multi-scale (county, township, and village) features of regional poverty in Yanbian Korean Autonomous Prefecture in Jilin province, China. It examined the impact of geographic capital and associated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…From a spatial perspective, the population, economy, and grain coupling coordination in the western and central counties of Jilin Province have gradually surpassed those of Jiangsu Province after 2010. This can be attributed to Jilin Province's excellent grain production conditions, evolving industrial structure [ 69 ], and advantageous resource endowments, including fertile black soil and favorable water and thermal conditions [ 70 ]. In contrast, the eastern counties of Jilin Province, situated near the Changbai Mountains [ 71 ], focus more on developing forestry economies [ 72 ], resulting in relatively poor conditions for grain production.…”
Section: Results and Analysismentioning
confidence: 99%
“…From a spatial perspective, the population, economy, and grain coupling coordination in the western and central counties of Jilin Province have gradually surpassed those of Jiangsu Province after 2010. This can be attributed to Jilin Province's excellent grain production conditions, evolving industrial structure [ 69 ], and advantageous resource endowments, including fertile black soil and favorable water and thermal conditions [ 70 ]. In contrast, the eastern counties of Jilin Province, situated near the Changbai Mountains [ 71 ], focus more on developing forestry economies [ 72 ], resulting in relatively poor conditions for grain production.…”
Section: Results and Analysismentioning
confidence: 99%
“…Since plenty of studies have explored how the proximity to PA boundary can affect locals' conservation attitudes and well-being (Naidoo et al, 2019;Carvache-Franco et al, 2021), it is worth paying attention (Kenneth, 2020). • Accessibility to main roads: as local residents spatially residing across the mountainous area mainly rely on the road traffic to travel to hospitals, schools, and other public facilities, the road accessibility may play an important part in shaping the fairness perceptions of residents (Wang et al, 2021). • Accessibility to tourism spots: the access to tourist attractions is potentially linked with benefits received from tourist attractions.…”
Section: Construction Of the Variable Set For Spatial Accessibilitymentioning
confidence: 99%
“…Several studies found it difficult to reduce impoverished people using traditional approaches and ideas when the government helped the poor out of poverty to a specific stage. The remaining impoverished people are concentrated in remote geographical areas with fragile ecological environments, outdated transportation infrastructure, and insufficient public facilities [17,18]. The lack of geographic capital in these regions leads to regional poverty [7], where the government must pull together with more targeted measures and extraordinary efforts.…”
Section: Introductionmentioning
confidence: 99%